A novel approach to include small reservoirs into a global hydrological model: Assessing its potential to reduce the agricultural water gap of smallholder farmers in Senegal - Anna C. Hoogeveen; Edwin H. Sutanudjaja; Gatien N. Falconnier; L.P.H. (Rens) van Beek; Niko Wanders; Marc F.P. Bierkens; Jannis M. Hoch (Journal of Hydrology: Regional Studies)
Study region: The country of Senegal Study focus: One consequence of climate change is shifting precipitation patterns towards shorter rainfall regimes, posing challenges to societies relying on agricultural activities. A possible avenue to alleviate the impact of climate change is the construction small-scale reservoirs to locally supply irrigation water for small-holder farmers. Here, we assess the ability of small-scale reservoirs to close the agricultural water gap in Senegal. To this end we introduce a method to find locations and capacities of small-scale reservoirs in a 1 km hyper-resolution global hydrological model that are most effective in minimizing the water gap. New hydrologic insights for the region: We find that the effect of small-scale reservoirs varies regionally, and that the optimum design does not close the water gap. More locally, the water gap can be reduced during the growing season, indicating that small-holder farmers in vicinity to such reservoirs can benefit. To close the remaining water gap, we assessed the feasibility of groundwater pumping. With pumping, the water gap can be closed, yet often only at the expense of sustainable groundwater use. Due to the novelty of the methods presented, this study should not provide any input to actual decisions. It shows, however, the potential of using hyper-resolution hydrological models for small-scale analyses. More practically, it highlights the immense challenges for societies affected by the climate crisis to meet their water demand in a sustainable way.